The Effect of CEO Overconfidence on Overinvestment: An Analysis of the Role of Inflation Uncertainty in the Capital Market - Hossein Alidadi; Mohammad Reza Abdoli; Farhad Dehdar (Iranian Journal of Finance, 2020)
Investment is seen as one of the most important and influential factors in economic growth and development. It is directly affected by managers' approaches to decision-making because identifying the best investment opportunities to achieve ideal returns is one of the expectations that shareholders and stakeholders have of managers to reduce agency gaps. However, the emergence of managers' overconfident behavior as a foundation for psychological bias can deepen the agency gap due to overestimating project cash flows compared to their real values under inflationary conditions. This study aims to examine the effect of inflation uncertainty on the impact managerial overconfidence has on overinvestment. The statistical population consists of companies listed on the Tehran Stock Exchange (TSE). One hundred five companies were selected as the sample size by systematic removal sampling reviewed in 2011-2018. Due to its dichotomous dependent variable, this study uses probit regression to test the research hypotheses. The results indicated the significant positive effect of CEO overconfidence on overinvestment. It was also noted that inflation uncertainty strengthens the positive effect of CEO overconfidence on overinvestment. Based on these results, the CEO's decisions as a decision-maker in charge of any company, especially under inflationary conditions, can play a substantial role in future corporate investment levels. Thus, with an increase in behavioral bias, it can be assumed that the company will confront grave competitive challenges under economic conditions.